IMPLEMENTASI SISTEM BUKITTINGGI GEMILANGSEBAGAI STRATEGI PERBAIKAN LAYANAN PUBLIK BERBASIS DIGITAL - Adria Fahyumi Alfanzha; Syamsir; Afifah Alya Syafira; Alimah Tusak Diyah; Alwi Abrar Rusli; Anisa Delia Safitri; Annisa Fadillah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Digital transformation in public service has become essential to ensure effective, transparent, and responsive governance. This study analyzes the implementation of the “Sistem Bukittinggi Gemilang” as a strategic effort to improve public services in Bukittinggi City by integrating multiple governmental services into a unified digital platform. The research employs a literature review and application feature analysis to assess the system’s relevance to public service needs. The findings indicate that the application enhances information accessibility, service efficiency, and accountability through transparent service data. It also strengthens public participation by providing reporting tools and centralized information channels. Nevertheless, challenges persist, including varying levels of digital literacy among citizens, government readiness, and the need to reinforce infrastructure and data security. This study highlights the importance of continuous system maintenance to ensure that digital innovation remains inclusive, sustainable, and aligned with public expectations.